Biopolymer films from pitahaya (Hylocereus sp.) cladodes: development and structural characterization toward the valorization of an underutilized pruning residue - Arroyo Esquivel, Laura (2026)
Biopolymer films (Bfs) were developed from pitahaya (Hylocereus sp.) cladodes, an abundant pruning residue that is currently underutilized due to handling and disposal constraints. In this study, we evaluated the individual and combined effects of glycerol (0–2% w/w), and cassava starch (0%–6% w/w) on film formation and performance using a casting approach. Films were characterized after 1 and 30 days of storage to assess physicochemical stability and structural changes. All formulations yielded continuous films with uniform macroscopic appearance and maintained structural integrity during storage. Color parameters (a∗, b∗, hue, chroma, and opacity) decreased over time, whereas luminosity was primarily influenced by starch content, with higher starch levels producing brighter films. Starch addition also increased film thickness and reduced moisture content, reflecting a more restricted water environment in the polymer matrix. Films with the highest starch content also exhibited increased water and acid solubility, whereas base solubility was unaffected by formulation. Mechanical testing revealed that films without glycerol had greater tensile strength, whereas those containing glycerol exhibited higher elongation at break, indicating enhanced flexibility. Water vapor permeability increased with glycerol and decreased with higher starch content, although all formulations remained more permeable than values commonly reported for low-density polyethylene. Thermal analysis by differential scanning calorimetry revealed stable glass transition and melting temperatures across formulation and storage time. X-ray diffraction showed decreased crystallinity with increasing glycerol and starch content, with further reductions after 30 days. Attenuated Total Reflectance–Fourier Transform Infrared Spectroscopy confirmed interactions among cladode polymers, glycerol, and starch, reflecting differences in hydrogen bonding and water retention. Overall, adjusting glycerol and starch levels allows for the modification of film properties, supporting the use of pitahaya cladodes as a raw material for biodegradable films.